Full repowering of existing fuel-oil fired power plant: Modeling and performance evaluation. (15th October 2022) - Kurbanoglu, Anil; Alagoz, Izzet; Elmali, Ayhan
Highlights: Ambarli Project is a full repowering by conversion to a combined cycle power plant. Ambarli Repowering Project is a first of its kind in Turkey. Official performance test results are used to validate the accuracy of the model. Overall repowered combined cycle block is modeled using Cycle-Tempo. Repowering has economic and environmental benefits while increasing power output. Abstract: Increasing electricity demand as a result of industrial development brings with it the need for larger installed power generation capacity. However, existing regulations, capital costs of new equipment, time-dependent constraints, and public opposition against building new power plants pose a strong challenge for greenfield power generation projects. These compelling factors have caused the repowering concept to gain importance again in recent years. Ambarli Repowering Project is a "Full Repowering by Conversion to Combined Cycle Power Plant" project that is the first of its kind in Turkey and is equaled in magnitude and complexity by only a handful of worldwide examples. In this context existing heavy fuel–oil fired steam power plant was repowered by conversion to natural gas fired combined cycle power plant. Here, in this paper, initial performance calculations of the existing steam turbine and achievable power output after rehabilitation are presented. Parameters such as inlet temperature, pressure, and steam mass flow are defined as boundary conditions for the model of the repowered Ambarli Power Plant that allows a comprehensive evaluation of the performance of the combined cycle power plant. An in-depth real case study is conducted to validate the outputs of the developed model by comparing them with the official performance test results. Results show that the total capacity of a conventional steam power plant can be increased by 203%, while the increase in heat rejection from the condenser is only 25%. Moreover, it is found that repowering has significant positive environmental effects such as reduction of NOX, SOX, and CO2 emissions in addition to economic benefits. Therefore, it is expected that this unique study, which has been validated with official performance tests, will shed light on similar projects to be made in the future.